Developing Banking Sector Strategies Amid Economic Turmoil - Steffi. R; S. Suman Rajest; R. Regin; Shynu T (Research Parks Publishers, 2023)
A shortage of bank liquidity precipitated the ongoing financial crisis that began in Large financial firms failed, and national governments stepped in to save banking systems and stock markets around the world. As the crisis escalated, it sent shockwaves throughout the global economy, causing a cascade of bank failures across Europe and a precipitous decline in the value of stocks and commodities. The purpose of this study is to analyse what led to the worldwide economic collapse. Recent scholarly work in the field of finance reveals that the enormous, unregulated credit default swaps market that emerged in the wake of the currency and banking crises was plagued by major mispricing difficulties due in large part to statistical models centred on optimistic expectations. This study examines the causes of and solutions to recent global financial crises, with a particular emphasis on how to strengthen the regulatory environment and reduce risk through recapitalization and emerging bank markets so as to avoid similar crises in the future.